Implementation of spatial data infrastructure for information sharing towards spatially enabled land administration in Malaysia - Hamzah, Abd Halim (2013)
The land administration activities related on land tenures, land values and land use towards computerised system aims to improve the land administration information sharing. Meanwhile, that activities need towards 2nd generation of spatial data infrastructure (process based model involve knowledge infrastructure, information sharing and more coordination). Nontechnical integration issues such as institutional, legislation and jurisdiction,structure and cultural human resources management practices, land information delivery services, and cross-government collaboration model also play an important role in information sharing. These issues have turned out to be the main problems in land administration information sharing between multiple level of government land administration agencies and also in countries with multiple level of government administration (federal, state and local). The idea is to implement the spatial data infrastructure concept to reduce issues of information sharing and produce better decision making towards spatial enabled land administration. This research chooses the qualitative method (interpretive research with ethnographic approach) and involves interview, observation and questionnaire. Analysis (with frequency statistic analysis and likert scale analysis) of the relevant issues in land administration information sharing practices with spatial data infrastructure was done. The targeted respondents were land administration (land use,land value and land ownership) government staff involved in the land administration information application and sharing practices. The major contribution of this research is the proposed Integrated Land Administration Information Sharing (ILaIS) model. Integrated with the capability information system, cooperation and steering committee, legislation and jurisdiction also spatially enabled land administration in ILaIS model is very helpful for land administrative purpose in the multiple level of government administration. The research findings based on the Delphi Method to validating the research contribution could act as a guideline for the making of policy, strategy and management for current land administration information sharing between the multiple level of government land administration agencies. It can modify the current policy and management strategy for greater effectiveness and efficiency; help to improve the integrated capability of information systems towards spatial enabled land administration.